Venture Capital Distributions: Short‐Run and Long‐Run Reactions - Gompers, Paul; Lerner, Josh (Journal of Finance, 1998)
Venture capital distributions, a legal form of insider trading, provides an ideal arena for examining the share price impact of transactions by informed parties. These sales, which occur after substantial run‐ups in share value, generate a substantial price reaction immediately around the event. In the months after distribution, returns apparently continue to be negative. When the short‐ and long‐run reactions are decomposed, they are consistent with the view that venture capitalists use inside information to time stock distributions: Distributions of firms brought public by lower quality underwriters and of less seasoned firms have more negative price reactions.